ASSOCIATION OF SMOKING STATUS, TYPE OF CIGARETTES AND OBESITY AS RISK FACTORS AMONG RENAL CELL CARCINOMA HISTOLOGICAL SUBTYPES - Pramod, Sawkar Vijay; El Haq, Faris; Safriadi, Ferry (Indonesian Journal of Urology, 2024)
Objective: This study aims to know the relationship between smoking and obesity as a risk factor among renal cell carcinoma histological subtypes. Material & Methods: This was a retrospective case-control study, with 67 patients with Renal Cell Carcinoma (RCC) at the Department of Urology, Hasan Sadikin Academic Medical Center Bandung from January 2012 to December 2021 as the case group, and 13 patients with benign tumors as the control group. The odds ratio and its significance were calculated. Results: In clear cell RCC, smokers (p-value=0.008), showed strong relationship to cigarette types (p-value=0.013), and obesity (p-value=0.042). In papillary RCC, smokers (p-value=0.035) showed a strong relationship to cigarette types (p-value=0.041). Cloves have a higher risk compared to filtered cigarettes (OR 2.25, 95% CI [0.54-9.25]). Conclusion: Clear cell RCC is most prevalent in smokers. Obesity is associated with clear cell RCC. Cloves pose the greatest risk of clear cell and papillary RCC. Keywords: Obesity, RCC, smoking, cigarette.